Educated Poznań Speech 30 years later - Kaźmierski, Kamil; Kul, Małgorzata; Zydorowicz, Paulina (Wydział Filologiczny UJ, 2019)
The study compares educated Poznań speech on the basis of a study by Witaszek-Samborska (1985, 1986) and a corpus compiled 30 years later. The features of Poznań speech, examined on 14 speakers from the corpus, include: voicing of obstruents before heterolexical sonorants (okszygemocji), realization of word-final ‹-ą› as [-ɔm] (idom tom drogom), realization of /stʂ tʂ dʐ/ as /ʂt͡ʂ t͡ʂ d͡ʐ/ (szczelać), the presence of the velar nasal [ŋ] before a heteromorphemic velar plosive /k/ (okienko), realization of word-final ‹-ej› as /-i(j)/ or /-ɨ(j)/ (lepi(j)), presence of prothetic [w] before word-initial /ɔ/ (łojciec), presence of voiced /v/ in clusters with preceding voiceless consonants (trwały), and realization of ‹-śmy› as [ʑmɨ] (słyszelˈiśmy). The results suggest a change in Poznań speech and point towards dialect levelling.
Keywords: Poznań speech; variability; language change; speech corpus; dialect leveling